Dampak La Nina pada Produksi dan Uji Banding Waktu Pangkas Vegetatif Tanaman Anggur (Vitis Vinifera) di Kota Palu - Ambinari Rachmi Putri; Kurdiyan Kurdiyan; Abd Syakur; Muhardi Muhardi (Stasiun Pemantau Atmosfer Global Lore Lindu Bariri - Palu, 2023)
Palu City, as a major grape – producing center, faced significant challenges due to the La Nina weather disturbance in mid – 2020, resulting in a decline in grape production. This research explores the impact of rainfall during La Nina on grape harvests and evaluates the differences in outcomes between plants pruned on December 1, 2020, and December 11, 2020. The study utilizes descriptive analysis and comparative testing (T – test) with two early vegetative pruning treatments on different dates. The results show a significant increase in rainfall in September 2020 during La Nina, leading to a decrease in grape production. However, there is no significant difference in the growth and yield of grape fruits between plants pruned on December 1, 2020, and December 11, 2020.